Cleaning of thick viscoplastic surface deposits using an impinging jet: Effect of process variables. (February 2020) - Tuck, Jessica P.; Alberini, Federico; Ward, Dick; Gore, Bill; Fryer, Peter J.
Abstract: Impinging jets are the tool of choice for cleaning mixing vessels. Layers of product can be left behind on the sides of these vessels. A range of thicknesses in the FMCG industries can be found; thick films are especially difficult to clean. Here data is presented for cleaning thick films (2–8 mm) with an impinging water jet. An imaging technique using ultra violet light has been developed to measure cleaning of these thick films as a function of time. Carbopol® 940 solution has been used as a model fluid, representing typical consumer goods, and food products. Cleaning takes place in four stages. For thick film cleaning, there is a delay between impingement and the start of cleaning, in which water is trapped below the deposit to form a blister. The time for the blister to burst was found to be a function of both deposit thickness and nozzle diameter. A stage of rapid cleaning was defined and analysed, with the rate of cleaning here correlating with the flow rate. There was mixed agreement when rapid cleaning data was fitted against previously reported cleaning models for thin films. Highlights: A detailed study of thick film cleaning using an impinging jet was conducted. A four stage cleaning mechanism for thick films has been identified. In the early stages of cleaning a surface blister is formed which bursts to start cleaning. A rapid stage of cleaning was identified and found to correlate with flow rate. Mixed agreement with thin film models was found.